2003
DOI: 10.1152/ajpregu.00162.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menstrual cycle on baroreflex control of heart rate: comparison with male volunteers

Abstract: This study was designed to determine baroreflex control of heart rate (HR) to hypotensive and hypertensive stimuli during the early follicular (EF), preovulation (PreOV), and midluteal (ML) phases of the menstrual cycle and to test the hypothesis that cardiovagal reflex responses to hypertensive stimuli would be altered depending on the plasma estradiol levels in healthy women. In addition, these results were compared with those of male volunteers. Fifteen healthy women with regular menstrual cycles and thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
77
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 30 publications
6
77
3
3
Order By: Relevance
“…Also, the augmented heart rate and sympathetic nerve responses in men could be the result of greater integrated baroreceptor unloading, as suggested by the larger drop in stroke volume. Nonetheless, the current data support earlier conclusions about attenuated cardiovagal baroreflex gain (1,38) and reduced heart rate responses to carotid baroreceptor stimulation (7) in women vs. men. Although cardiovagal and sympathetic baroreflex control may be affected by menstrual cycle (8,28), it is unclear whether this effect can overwhelm the overall difference between male and female orthostatic responses (36).…”
Section: Discussionsupporting
confidence: 91%
“…Also, the augmented heart rate and sympathetic nerve responses in men could be the result of greater integrated baroreceptor unloading, as suggested by the larger drop in stroke volume. Nonetheless, the current data support earlier conclusions about attenuated cardiovagal baroreflex gain (1,38) and reduced heart rate responses to carotid baroreceptor stimulation (7) in women vs. men. Although cardiovagal and sympathetic baroreflex control may be affected by menstrual cycle (8,28), it is unclear whether this effect can overwhelm the overall difference between male and female orthostatic responses (36).…”
Section: Discussionsupporting
confidence: 91%
“…Greenberg et al 11 , Hirshoren et al 12 and Pai et al 13 also have demonstrated similar findings. Again, sato et al 1 observed similar results when compared SBP and DBP during follicular and luteal phases of menstrual cycle.…”
Section: Discussionmentioning
confidence: 61%
“…Significant correlations were observed between plasma estradiol concentrations and BRS assessed by the phenylephrine method and the Valsalva maneuver. 24 Sevre et al demonstrated a significantly lower BRS in hypertensive subjects than in normotensive controls. 15 Moreover, the reduction in BRS was most pronounced in the female group and did not reach statistical significance in men.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, it has been previously reported that baroreflex-mediated control of heart rate is altered during the normal menstrual cycle. 24 The baroreflex-mediated bradycardic response was augmented during the preovulatory phase and appeared to correlate with the plasma estradiol concentration, whereas baroreflex-mediated tachycardia was augmented during the early follicular phase. Significant correlations were observed between plasma estradiol concentrations and BRS assessed by the phenylephrine method and the Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 95%